T-Cell Therapeutics Targeting Human Parainfluenza Virus 3 Are Broadly Epitope Specific and Are Cross Reactive With Human Parainfluenza Virus 1 - Harris, Katherine M.; Horn, Sarah E.; Grant, Melanie L.; Lang, Haili; Sani, Gelina; Jensen-Wachspress, Mariah A.; Kankate, Vaishnavi V.; Datar, Anushree; Lazarski, Christopher A.; Bollard, Catherine M.; Keller, Michael D. (Frontiers in Immunology, 2020)
Human Parainfluenza Virus-3 (HPIV3) causes severe respiratory illness in immunocompromised patients and lacks approved anti-viral therapies. A phase I study of adoptively transferred virus-specific T-cells (VSTs) targeting HPIV3 following bone marrow transplantation is underway (NCT03180216). We sought to identify immunodominant epitopes within HPIV3 Matrix protein and their cross-reactivity against related viral proteins. VSTs were generated from peripheral blood of healthy donors by ex-vivo expansion after stimulation with a 15-mer peptide library encompassing HPIV3 matrix protein. Epitope mapping was performed using IFN-g ELIspot with combinatorial peptide pools. Flow cytometry was used to characterize products with intracellular cytokine staining. In 10 VST products tested, we found 12 novel immunodominant epitopes. All products recognized an epitope at the C-terminus. On IFN-γ ELISpot, individual peptides eliciting activity demonstrated mean IFN-γ spot forming units per well (SFU)/1x10^5 cells of 115.5 (range 24.5-247.5). VST products were polyfunctional, releasing IFN-γ and TNF-α in response to identified epitopes, which were primarily HLA Class II restricted. Peptides from Human Parainfluenza Virus-1 corresponding to the HPIV3 epitopes showed cross-reactivity for HPIV1 in 11 of 12 tested epitopes (mean cross reactivity index: 1.19). Characterization of HPIV3 epitopes may enable development of third-party VSTs to treat immune suppressed patients with HPIV infection.